Non-invasive Ventilation for Pediatric Hypoxic Acute Respiratory Failure Using a Simple Anesthetic Mask With 3D Printed Adaptor: A Case Report - Muller, Gerrit J.; Hovenier, Renee; Spijker, Jip; van Gestel, Monica; Klein-Blommert, Rozalinde; Markhorst, Dick; Dijkman, Coen; Bem, Reinout A. (Frontiers in Pediatrics, 2021)
Non-invasive ventilation (NIV) is increasingly used in the supportive treatment of acute respiratory failure in children in the pediatric intensive care unit (PICU). However, finding an optimal fitting commercial available NIV face mask is one of the major challenges in daily practice, in particular for young children and those with specific facial features. Large air leaks and pressure-related skin injury due to suboptimal fit are important complications associated with NIV failure. Here, we describe a case of a four-year old boy with cardiofaciocutaneous syndrome and rhinovirus-associated hypoxic acute respiratory failure who was successfully supported with NIV delivered by a simple anesthetic mask connected to a headgear by an in-house developed and 3D printed adaptor. This case is an example of the clinical challenge related to pediatric NIV masks in the PICU, but also shows the potential of alternative NIV interfaces e.g. by using a widely available and relatively cheap simple anesthetic mask. Further personalized strategies (e.g. by using 3D scanning and printing techniques) that optimize NIV mask fitting in children are warranted.